A Posted-Price Auction for Heterogeneous Spectrum Sharing under Budget Constraints - Wen-Hsiang Lai; Pavol Polacek; Chih-Wei Huang (EAI Endorsed Transactions on Wireless Spectrum, 2016)
The concept of cognitive radio is emerging as a platform for designing next generation wireless networks with dynamic resource sharing among machines. However, how to efficiently and fairly share the spare channels is still a topic under intensive research. This paper investigates a spectrum trading problem under relatively realistic settings, where heterogeneous channels under buyers' budget constraints are specifically considered, while maintaining incentive compatibility and individual rationality. The proposed auction game consists of a price-setting primary owner (PO), targeting on maximizing its total revenue, and secondary users (SUs), bidding channels for reasonable values. To handle channel heterogeneity, SUs provide independent valuation according to observed quality on different channels. The PO adopts a sequential arbitrary-order mechanism for flexible deployment and achieving aforementioned economic properties in polynomial time. Finally, the numerical results show performance improvements in PO revenue and SU utility over reference approaches.